Numerical simulation of heat transfer in a canine knee joint in thermal neutrality: analysis of the influence of different values of blood perfusion and considerations of the blood perfusion rate (Bioscience Journal, 2016)
This study aimed to simulate heat transfer in thermal equilibrium in the canine knee joint. We analyzed the impact of different values of blood perfusion available in the literature and considered blood perfusion rates. The geometric models of canine knee joints were created from a photographic record of a cross section of an anatomical part. Two geometric models were developed: one without the epidermis and one with the epidermis. A heat diffusion equation was used to model the heat transfer phenomenon. Numerical simulations of the canine knee in a thermal neutrality condition were performed using the ANSYS-CFX® program. The simulation results were compared with experimental in vivo data. The smaller percentage differences between the experimental and simulated in vivo results were found in simulations that used the blood flow rate as a function of temperature. The computer simulation proved to be a good alternative to evaluate the temperature of biological tissues.